Waste Recycling Strategy and its Role in Enhancing the Dimensions of Sustainable Development in Iraq - H. Kzar , Mustafa; Shakir Muslim, Hamdiyah (Journal of Economics and Administrative Sciences, 2024)
Purpose: The aim of this study was to determine the importance of waste recycling in addressing economic, social and environmental problems facing most countries of the world, especially developing countries, including Iraq, Where Iraq has not developed a recycling strategy for waste considering the economic and climatic changes that the world is witnessing with the increase in population growth rates and the expansion of cities. Theoretical Framework: Many economists, such as (Kirrchher J., & et al., 2017; Murray, A., & et al., 2015; Prieto-Sandoval V. & et al., 2018; Williams, 2013) have also highlighted the importance of practices in production and waste management, to provide a new business model and a new economic system, by linking economic activity to the extraction of natural resources and starting to introduce a way of thinking that uses waste efficiently and achieves economic optimization. Design/Methodology/Approach: We have clarified the recycling strategy for waste in Iraq based on the deductive and inductive approach, using descriptive analysis in order to study the recycling process of waste, and its relationship in promoting sustainable development in Iraq. Findings: Iraq is facing the problem of waste accumulation and worsening environmental pollution. The government should keep pace with the global development in the exploitation of waste as an economic resource and exploit it in the field of energy generation through the establishment of governmental and non-governmental projects specialized in the process of recycling waste, to achieve economic, social and environmental benefits, to achieve the dimensions of sustainable development in Iraq. Research, Practical & Social Implications: The practical implications include recommendations for economic policy makers to promote sustainable development by adopting measures that support waste recycling in Iraq, and encouraging investments in this process that enhances the environment and economic development. The study’s insights can help formulate economic policies that increase the sustainable development rates of bilateral resources and address environmental and economic challenges. Originality/Value: The originality and scientific value of the study lie in the comprehensive analysis of the role of waste recycling and its relationship to sustainable development in Iraq. It explores the areas of potential application of recycling and its levels in Iraq and provides practical recommendations to promote sustainable development. The study’s approach ensures a deductive analysis of the relationship between waste recycling and sustainable development.